The chase : a novel - Evanovich, Janet; Goldberg, Lee, 1962- (New York, NY : Bantam, 2014)
Internationally renowned thief and con artist Nicolas Fox is famous for running elaborate and daring scams. His greatest con of all: convincing the FBI to team him up with the only person who has ever caught him, Special Agent Kate O'Hare. Together they'll go undercover to swindle and catch the world's most wanted and untouchable criminals. Their newest target is Carter Grove, a former White House chief of staff and the ruthless leader of a private security agency. Grove has stolen a rare Chinese artifact from the Smithsonian, a crime that will torpedo U.S. relations with China if it ever becomes public. Nick and Kate must work under the radar and against the clock to devise a plan to steal the piece back. Confronting Grove's elite assassins, Nick and Kate rely on the skills of their ragtag crew, including a flamboyant actor, a Geek Squad techie, and a band of AARP-card-carrying mercenaries led by none other than Kate's dad.
Keywords: United States. Federal Bureau of Investigation -- Fiction; Swindlers and swindling -- Fiction; Suspense fiction